Innovation management strategies for industrial machinery maintenance: Enhancing competitive advantage - Siangwong, Phusit; Chienwattanasook, Krisada (Edelweiss Applied Science and Technology, 2025)
In a rapidly evolving technological and business environment, business leaders must adapt quickly to maintain their competitiveness. The main objective of this article is to propose a maintenance management guide with the innovation management process to help organizations develop effective innovation strategies and respond to the challenges of the Industry 4.0 era. It examines the principles and strategies of innovation management in the maintenance of industrial machinery and their impact on competitiveness. It focuses on the integration of digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data analytics into maintenance processes. This article explains that the introduction of modern technologies in the areas of predictive maintenance, condition-based maintenance, and intelligent maintenance significantly reduces machine downtime, increases production efficiency, and lowers operating costs. However, implementing these innovations comes with challenges, including data management, cybersecurity risks, lack of employee skills, and high investment costs, especially for small and medium-sized enterprises (SMEs). This article proposes a structured transition plan for the introduction of innovative maintenance strategies. The approach focuses on upskilling the workforce and cultivating an innovation-oriented corporate culture. By addressing these challenges, companies can strengthen their competitiveness and long-term sustainability in an increasingly digitalized industrial landscape.